Molecular targeted therapies in non-GIST soft tissue sarcomas: what the radiologist needs to know - Tirumani, Sree Harsha (e-Med, 2013)
Non-gastrointestinal stromal soft tissue sarcomas are uncommon neoplasms that have a dismal prognosis due to a high incidence of metastases and a poor response to conventional chemotherapy. The identification of characteristic genetic alterations in several of these tumors has opened the window for molecular targeted therapies in patients who have failed conventional chemotherapy. Imaging plays a critical role in assessing the response to these novel therapeutic agents. Just like the response of gastrointestinal stromal tumors to imatinib, the response of non-gastrointestinal stromal soft tissue sarcomas to molecular targeted drugs is better evaluated on imaging by alternate tumor response criteria such as the Choi criteria. In addition, these drugs are associated with distinct class-specific drug toxicities that can come to attention for the first time on imaging. The purpose of this article is to provide a primer for the radiologist on the various molecular targeted therapies in advanced/metastatic non-gastrointestinal stromal soft tissue sarcomas with emphasis on the role of imaging in assessing treatment response and complications.